Determination of Enterprise Risk Management Disclosure by Audit Committee, Company Scale, and Leverage - Edward, Mohammad Yunies; Hidayah, Lailatul (Jurnal Rekognisi Akuntansi, 2024)
Corporate risk management disclosure is an effort made by companies to provide information about potential threats to the continuity of their business. This disclosure aims to monitor management activities and reduce fraud in annual financial reports. This study aims to empirically test the effect of the audit committee, company size, and leverage on risk management disclosure in manufacturing companies listed on the Indonesia Stock Exchange during the 2016-2019 period. The population of this study includes manufacturing companies listed on the Indonesia Stock Exchange during that period. Sampling was carried out using the purposive sampling method, resulting in 404 analysis units. Data analysis was carried out using panel data regression with the help of EViews software. The results of the study indicate that company size has a significant positive effect on risk management disclosure in manufacturing companies listed on the Indonesia Stock Exchange. On the other hand, the audit committee and leverage do not show a significant effect on risk management disclosure in the same company.